Reciclando e aprendendo - Rodrigues, Hiaçanã Oliveira; Dornelas, Ocidália Dourado; Penso, Rosely Soares Brandão; Silva, Roniscleide Souza; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf